In Vitro Studies of Anti-Hemolytic and Cytotoxic Activity of Procyanidin-Rich Extract from the Leaves of Actinidia arguta - Cyboran-Mikołajczyk Sylwia; Csonka Ákos; Molnar Joseph; Szabó Diana; Oszmiański Jan; Kleszczyńska Halina (Polish Journal of Food and Nutrition Sciences)
The leaves of mini kiwi (Actinidia arguta) are a rich source of phenolic compounds, in particular the B-type procyanidins that exhibit e.g. antioxidant, anticancer, antiviral, and anti-inflammatory activities. The aim of this study was to determine the biological activity of the extract from leaves of kiwi in relation to cells of erythrocytes and lymphoma. This activity was determined by studying kiwi leaves extract anti-hemolytic, cytotoxic and antiproliferative activity, and its ability to change the physical properties of the cell membrane and inhibit multidrug resistance of mouse lymphoma cells. It was shown that the extract ingredients bound to the cells, caused changes in erythrocyte shape and slightly affected the granularity and size of lymphoma cells. They effectively protected the red blood cells from oxidative damage, but were not toxic to lymphoma cells and did not affect their multidrug resistance. The extract of kiwi leaves is an effective antioxidant but it does not exhibit cytotoxic activity. Therefore, it can be used in the prevention of diseases, especially those related to oxidative stress.